Predicted and remembered emotion: tomorrow's vividness trumps yesterday's accuracy. Issue 1 (2nd January 2020) - Levine, Linda J.; Lench, Heather C.; Stark, Craig E. L.; Carlson, Steven J.; Carpenter, Zari K.; Perez, Kenneth A.; Stark, Shauna M.; Frithsen, Amy
ABSTRACT: People rely on predicted and remembered emotion to guide important decisions. But how much can they trust their mental representations of emotion to be accurate, and how much do they trust them? In this investigation, participants ( N  = 957) reported their predicted, experienced, and remembered emotional response to the outcome of the 2016 U.S. presidential election. They also reported how accurate and vivid they perceived their predictions and memories to be, and the importance of the election. Participants remembered their emotional responses more accurately than they predicted them. But, strikingly, they perceived their predictions to be more accurate than their memories. This perception was explained by the greater importance and vividness of anticipated versus remembered experience. We also assessed whether individuals with Highly Superior Autobiographical Memory for personal and public events ( N  = 33) showed superior ability to predict or remember their emotional responses to events. They did not and, even for this group, predicting emotion was a more intense experience than remembering emotion. These findings reveal asymmetries in the phenomenological experience of predicting and remembering emotion. The vividness of predicted emotion serves as a powerful subjective signal of accuracy even when predictions turn out to be wrong.